Solar energy for preheating ventilating air - C K Spillman; F V Robbins; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1977)
The basic concept of the solar energy collector- storage system for preheating ventilating air is sound, and it should be an economic alternative as energy becomes less available and/or more expensive. Based on current energy prices it can't be justified on a strict economic basis without large tax credits. We plan to continue research, working with other scientists, to develop it so that functional and reliable units can be constructed when our national energy situation demands such a solar energy system.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Solar energy; Preheating ventilating air